ADDRESSING ICT IMPLEMENTATION CHALLENGES IN RICE EXTENSION SERVICES IN BENUE AND NIGER STATES. - Umar , Ahmed (Ayden Journal of Agriculture and Allied Studies, 2024)
This study was carried out to investigate the constraints to application of selected information and communication (ICT) technologies in extension service delivery among rice farmers and extension workers in Benue and Niger States, Nigeria. Adopting a multistage sampling technique in four stages, 202 respondents were selected to form the sample size. Data were collected using a well-structured questionnaire, and analyzed using both descriptive and inferential statistics, particularly frequency, percentage, mean, standard deviation, Mann-Whiney, Chi-square and Factor analysis. Findings revealed that there was no significant relationship between level of knowledge in application of selected ICT by the respondents X2 Cal = 2.86 < X2 Tab = 5.991) at 0.05 level of probability. Results also indicated that there were three categories of constraints, namely socio-economic constraints (Factor 1), environmental constraints (Factor 2) and administrative constraints (Factor 3). Provision of internet network; procurement and installation of ICTs and supportive services in all ADPs should be assured. Also, the constraints to application of ICT should be addressed by the government